Proteomic analysis reveals the difference between the spermatozoa of young and old Sus scrofa - Shuhao Fan; Fan Xie; Qianqian Wang; Haibo Ye; Yali Tian; Yangguang Liu; Huibin Zhang; Xianrui Zheng; Zongjun Yin; Xiaodong Zhang (Scientific Reports)
Abstract The Wannan black pig is a superior local breed in Anhui province, renowned for its exceptional meat quality and remarkable adaptability to various environmental conditions. Semen, being a crucial indicator of male sexual maturity and fertility, significantly influences the performance of breeding boars. The molecular basis for comprehending the fecundity of boars in practical production lies in understanding the disparities in sperm proteins among boars of varying ages. In this investigation, spermatozoa from three one-year-old and three seven-year-old Wannan black pigs were individually chosen. Employing a tandem mass tag (TMT)-based quantitative proteomics approach, a total of 4050 proteins were identified, out of which 130 proteins exhibited significant differences between the two groups. GO enrichment analysis revealed that these proteins primarily participated in energy metabolism, spermatogenesis, fertilization, and reproduction. KEGG enrichment analysis demonstrated that the differential proteins predominantly resided within the ribosome pathway. A protein-protein interaction (PPI) network was constructed to identify core proteins such as Small ribosomal subunit protein uS7 (RPS5). Ultimately, parallel reaction monitoring (PRM) was conducted on the selected differential proteins to validate result accuracy. The findings of this study establish a foundation for elucidating the molecular mechanism underlying variations in spermatozoa protein levels among Wannan Black Pig with different age.